Pengaruh Profitabilitas, Leverage, Likuiditas, dan Kepemilikan Manajerial terhadap Financial Distress - Handayani, Damia Fitri; Wuryani, Eni (STIE Perbankan Indonesia, 2025)
This study aims to investigate and analyze the impact of profitability, leverage, liquidity, and managerial ownership on financial distress in banking companies listed on the Indonesia Stock Exchange. The secondary data used in this study comes from 47 banking companies that have consistently been listed during the 2020-2023 period and passed the purposive sampling test. The analysis technique employed is multiple linear regression using SPSS software. The results show that the variables of profitability, liquidity, and managerial ownership have a positive impact on financial distress, while leverage does not show a significant effect. These findings indicate that careful risk management and the implementation of good corporate governance are crucial to prevent potential financial problems in the banking sector, particularly in maintaining financial stability and the long-term sustainability of companies. Keywords: Financial Distress, Profitability, Leverage, Liquidity, Managerial Ownership